2017
DOI: 10.1242/dev.148684
|View full text |Cite
|
Sign up to set email alerts
|

A radial axis defined by semaphorin-to-neuropilin signaling controls pancreatic islet morphogenesis

Abstract: The islets of Langerhans are endocrine organs characteristically dispersed throughout the pancreas. During development, endocrine progenitors delaminate, migrate radially and cluster to form islets. Despite the distinctive distribution of islets, spatially localized signals that control islet morphogenesis have not been discovered. Here, we identify a radial signaling axis that instructs developing islet cells to disperse throughout the pancreas. A screen of pancreatic extracellular signals identified factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 106 publications
0
26
0
Order By: Relevance
“…It remains possible that single-cell directional migration guides new endocrine cells to established islets later during postnatal growth and in adulthood, when the rate of new cell emergence is dramatically reduced ( Ackermann and Gannon, 2007 ). Movement of islets away from the duct may occur through a combination of exocrine tissue expansion and active directional migration ( Pauerstein et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It remains possible that single-cell directional migration guides new endocrine cells to established islets later during postnatal growth and in adulthood, when the rate of new cell emergence is dramatically reduced ( Ackermann and Gannon, 2007 ). Movement of islets away from the duct may occur through a combination of exocrine tissue expansion and active directional migration ( Pauerstein et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, owing to the experimentally inaccessible location of the pancreas in humans and most animal models, relatively little is known about the cellular dynamics and molecular mechanisms controlling islet morphogenesis. As single endocrine cells as well as clusters have been identified in pancreatic mesenchyme, islet formation has been postulated to involve cell migration in response to external directional cues ( Cole et al, 2009 ; Puri and Hebrok, 2007 ; Pauerstein et al, 2017 ). However, the finding of islet clusters forming in close proximity to the ductal epithelium ( Bader et al, 2016 ; Kesavan et al, 2014 ; Pan and Wright, 2011 ) suggests that cell interactions at close distances might contribute to islet formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It recently was shown that a double deletion of Robo1 and Robo2 in lung pulmonary neuroendocrine cells (PNECs) results in the loss of PNECs’ clustered architecture 34 . The delamination, migration and aggregation of the islets of Langerhans involve several Robo-related neuronal proteins such as Semaphorin, Ephrin/Eph and N-CAM 35 40 , as well as direct signals from the nervous system 41 . Moreover, Robo receptors themselves have been implicated in collective cell movement during organogenesis in various mammalian tissues 42 , 43 .…”
Section: Introductionmentioning
confidence: 99%
“…For islet proliferation analysis and representative images presented in this manuscript, fluorescent micrographs were captured with a 40x objective lens. Images were processed in Image J for islet cell mass quantification and Image-Pro Plus for islet cell proliferation using previously described methods [60][61] .…”
Section: Human Islet Procurement and Transplantationmentioning
confidence: 99%